Conjugation of polymer with gold nanoparticles to mediate high performance non-fouling tuberculosis sensing - Anniebell A/P Stanley (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
This research encompasses the polymer conjugated gold nanoparticles (GNP) in mediating non-biofouling detection of 16 kDa antigen of tuberculosis. Polymer conjugated GNP is highly regarded because of the extensive proof of their unique properties of biological inertness and low levels of cytotoxicity. This enables the inhibition of biofouling in biosensors which is an occurrence that takes place as cellular and protein like biological elements accumulate on the detection surface and leads to an inaccurate biosensor output. Densely packed repeating chains of polymers such as polyethylene glycol (PEG) are capable of decreasing non-specific reactions of proteins. Among the applications of polymer conjugated GNPs in the field of biomedicine are as delivery agents, cancer therapeutic functions and in imaging functions. The fabrication of a 16 kDa antibody immobilized nanogap chip that simulates a biosensor mechanism involves a number of studies including the parametric effects such as type of gold GNP, type of PEG, concentration of PEG, concentration of Aminopropyltriethoxysilane (APTES) and 16 kDa antibody. GNP was chosen in comparison to gold nanorods due to a higher sensitivity and minimum reagent requirements. Polyethylene Glycol bpoly( acrylic acid) of concentration 1 mg/mL was also proven to be optimum for conjugation with GNP. Subsequently, the highest sensitivity was exhibited by nanogap chip with 2% APTES and 200 nM 16 kDa antigen. The success of PEG conjugated GNP is proved by the improved sensitivity in impedance reading of PEG conjugated GNP nanogap chip by picoammeter analyses as compared to the 16 kDa antigen detection by the sensor without the presence of PEGylated GNP.